Is traditional retail moving to e-commerce in the field of the fashion industry in India? - Saravanan, Raja (2019)
The main aim of this dissertation is to discover whether consumers feel that e-commerce provides superior performance and technology facilities than traditional retail from the perspective of Indian consumers, and to assess the importance of Omni-channel concepts and operations in the fashion industry. The fashion industry is one of the foremost business segments in India. Currently, the fashion industry is overcoming with new technology and innovation in their business. In the 1990s e-commerce was introduced saw the potential possibilities of innovation, and the new concepts which made the consumer base attractive towards e-commerce. Online retailers are growing faster than traditional retailers due to high pressure from online retailer’s offers and strategies. This research is identifies the issues in the fashion retail business in India. What are the challenges faced by traditional retail? What are the environmental causes disturbing the fashion retail industry which are argued with more detail in PEST analysis and Porter’s five forces of modern retailing and communication? Traditional fashion retailers understand how to solve difficulties and challenges in the supply chain. Discussed many technologies for fashion retail markets to improve their strategy and customer satisfaction. Researching the hypotheses are collecting behaviourism, functionalism, and experimental ideas what should traditional retailers do in their retail shop and which channel should they adopt for their business? Hypotheses are used to conduct a quick market analysis to understand the Indian demographic attitudes towards technologies, client interest, and Omni-channel. We need to understand which approaches we can use to gain knowledge in theoretical perspective. Multiple techniques are involved in the analysis and validation of hypotheses. I used SPSS tool for data analysis with cross-tabulation function. In this research I found that traditional retail and e-commerce are independent of each other but gradually merging, a most important factor for future fashion industry trends. They are systematically embracing Omni-channel strategy to provide good consumer service.